Influence of off-season land management on maximizing yield and quality of Curcuma longa L. cultivars - ANBURANI, A. (Journal of Phytology, 2018)
The present investigation was carried out to study the effect of off season soil management practices on yield and quality of turmeric (Curcuma longa L.) cultivars. The experiment was laid out in a Factorial Randomized Block Design with ten treatments in three replications consisted of five off-season land management treatments viz., fallow (S1), summer ploughing 2 times (S2), summer ploughing 1 time (S3), solarization with transparent polyethylene film of 0.05 mm thick for 40 days (S4) and black polyethylene film for 40 days (S5). It was tested with two popular cultivars viz., Curcuma longa -1 CL-1 (V1) and Curcuma longa-2 CL-2 (V2), collected from Erode and Chidambaram. Various yield components were recorded at the time of harvest and were analysed. The yield attributing characters viz., number, length, girth and weight of mother, primary and secondary rhizomes were recorded. The treatment where solarization with transparent polyethylene film of 0.05 mm thick was tested recorded the highest yield and yield attributing characters when compared to other treatments. The same treatment also exhibited the highest fresh rhizome yield per plant, curing percentage and cured rhizome yield. The quality parameters like curcumin, oleoresin and essential oil content were also showed superior performance in the treatment where solarization with transparent polyethylene film of 0.05 mm thick was applied.